Religion and extremism: rejecting diversity - Pratt, Douglas (Bloomsbury Academic, 2018)
Accommodating diversity: paradigms and patterns -- Diversity resisted: exclusion and fundamentalism -- Texts of terror: scriptural motifs for extremism -- The Jewish experience of extremism -- Forms of Christian extremism -- Trajectories of Islamic extremism -- Mutual extremism: reactive co-radicalization -- Extremism and Islamophobia